175k views
1 vote
alochΣ(1-1)6. Expand0 + (-1) + (-2) + (-3) + (-4) + (-5)1+ 2 + 3 + 4 + 5 + 60 + 1+ 2 + 3 + 4 + 5(-1) + (-2) + (-3) + (-4) + (-5) + (-6)

alochΣ(1-1)6. Expand0 + (-1) + (-2) + (-3) + (-4) + (-5)1+ 2 + 3 + 4 + 5 + 60 + 1+ 2 + 3 + 4 + 5(-1) + (-2) + (-3) + (-4) + (-5) + (-6)-example-1
User Rafy
by
6.0k points

1 Answer

2 votes

Expand


\sum ^6_(n\mathop=1)(1-n)\text{ indicates that we w}ill\text{ substitute values of n from 1 to 6 and find their sum}

Substitute when n=1

We will have that (1-n)


\begin{gathered} (1-n)=(1-1)=0 \\ \text{when n= 2} \\ (1-n)=(1-2)=-1 \\ \text{when n=3} \\ (1-n)=(1-3)=-2 \\ \text{when n=4} \\ (1-n)=(1-4)=-3 \\ \text{when n=5} \\ (1-n)=(1-5)=-4 \\ \text{when n=6} \\ (1-n)=(1-6)=-5 \end{gathered}

Therefore,


\begin{gathered} \sum ^6_(n\mathop=1)(1-n)= \\ =0+(-1)+(-2)+(-3)+(-4)+(-5) \end{gathered}

Hence,

The correct option would be the first option A

User Kamran Ali
by
5.4k points